An Analytic Hierarchy Process Approach in Decision-Making for Material Selection in an Automotive Company: A Case Study - Jack Kie, Cheng; Khalif Hassan, Ahmed; Mohd Aripin, Norhana; Mohd Yunus, Rafiuddin (KnE Social Sciences, 2019)
This study is an approach to investigate and to choose the suitable material for the fabrication of tools trolley to ensure the good quality of the product. The project team of an automotive manufacturing company is planning to fabricate 100 sets of tools trolley in the assembly shop. This study was developed to describe an approach based on Analytic Hierarchy Process (AHP) that can assist decision-makers and continuous improvement engineers in determining the most suitable material to be employed in fabrication process at the early stage of the product development to reduce the cost. The selected main criteria are Material Strength, Material Cost, Procurement Lead Time and Duration of Fabrication Process while the four materials that will be considered in this study are Aluminium, Steel Tube, and Square Tube. Finally, the results show that Square Tube is recommended as the most suitable material for the in-house tools for trolley fabrication.